Reaction of aromatic nitroso compounds with chemical models of thiamin active aldehyde - Ferreira, L. M. (2020)
Aromatic nitroso compounds in the presence of base and 2-(a-hydroxyalkyl)-3,4-dimethylthiazolium trifluoromethanesulfonate and related salts furnish in variable yields O- and N-acyl-aryl hydroxylamines and 3,4-dimethylthiazolium trifluoromethanesulfonate. A primary kinetic isotope effect of 4.9, obtained for the appropriate 2a-deuterated thiazolium salt, points to the C2a–H bond cleavage as the rate de- termining step. Radical species detected by ESR were unambiguously identified as phenylhydronitroxide, but attempted trapping of the corresponding C–heterocyclic radicals by TEMPO was not successful, and substrates incorporating a potential cyclopropyl radical clock gave products with the cyclopropyl ring intact. Theoretical calculations revealed a large activation energy for such reaction, which thus cannot per se exclude the intervention of such radical species. Evidence for the likely operation of two con- current mechanisms, a radical and a preponderant ionic pathway, involving the conjugate base of the thiazolium salt, as the chemical model for ‘active thiamine’, and ArNO is presented for the formation of the products of the reaction.